Identifikasi lingkungan perairan untuk budi daya karang hias di desa Arakan Kabupaten Minahasa Selatan - Manembu, Indri S; Ngangi, Edwin L.A (e-Journal BUDIDAYA PERAIRAN, 2016)
This research aimed to gather data and information as well as to evaluate the waters condition and water quality suitable for ornamental coral aquaculture, so the characteristic of Arakan waters for ornamental coral aquaculture could be examined.  The research applied Explorative Descriptive method with Purposive Sampling.  Research stations were established at 20 points representing the overall ecosystem of Arakan waters.  Data collected  consisted of physical conditions (bottom substrate, flow rate, turbidity, water depth, salinity, temperature, TSS) and  chemical conditions (pH, DO, nitrate, phosphate). Data were analyzed using Matching Method by matching the data obtained from sea water standard quality table for marine biota in accordance to Kep.Men. LH No. 51/2004 and data from Hutabarat and Evans (1984).  Based on physical and chemical conditions, Arakan waters was suitable for ornamental coral aquaculture or categorized as suitable. However, water temperature at the time of measurement was not proper,  thus monitoring of this parameter for longer period was required. Keywords: Arakan Village, ornamental coral, water quality, waters condition,  matching                      method